2022
DOI: 10.3389/fphys.2022.863380
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Genes Regulate Temperature-Dependent Diapause Induction in Silkworm Bombyx mori

Abstract: The bivoltine strain of the domestic silkworm, Bombyx mori, exhibits a facultative diapause phenotype that is determined by maternal environmental conditions during embryonic and larval development. Although a recent study implicated a circadian clock gene period (per) in circadian rhythms and photoperiod-induced diapause, the roles of other core feedback loop genes, including timeless (tim), Clock (Clk), cycle (cyc), and cryptochrome2 (cry2), have to be clarified yet. Therefore, the aim of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…In a recent study, a Per ‐knockout strain of Bombyx mori lost the ability to enter photoperiod‐induced embryonic diapause 24 . Moreover, temperature‐dependent embryonic diapause can be disturbed by knockout of Tim or Per gene in Bombyx mori 25 . Although H. armigera diapauses in the pupal stage are different from silkworm, our results suggest that the clock gene Tim is involved in diapause induction in H. armigera .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In a recent study, a Per ‐knockout strain of Bombyx mori lost the ability to enter photoperiod‐induced embryonic diapause 24 . Moreover, temperature‐dependent embryonic diapause can be disturbed by knockout of Tim or Per gene in Bombyx mori 25 . Although H. armigera diapauses in the pupal stage are different from silkworm, our results suggest that the clock gene Tim is involved in diapause induction in H. armigera .…”
Section: Discussionmentioning
confidence: 56%
“…Diapause has been observed in diverse embryonic stages, larval instars, pupae, and adults; however, for any given species, the potential for diapause is usually restricted to a single stage 20 . Insect photoperiodism is closely linked to circadian clock 21–25 . Insect circadian clocks may measure the photoperiod and temperature and translate this information into downstream endocrine signals 18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6A). The diapause-associated changes to circadian gene expression—such as the upregulation of period and downregulation of clock— was observed through our analysis, suggesting our experimental design accurately represents diapause physiology (Salminen et al, 2015; Homma et al, 2022). In addition, JH-responsive genes Obp99a and Fad2 showed expected changes in transcription according to the presence or absence of S-methoprene, demonstrating the success of our supplementation approach (supplemental fig.…”
Section: Resultsmentioning
confidence: 71%
“…Our results agree with Ikeda et al (2021) that found that knocking out per in Kosetsu, another bivoltine strain, inhibits the diapause egg production induced by a short-day condition during the larval stage. Recently, Homma et al (2022) reported that core clock genes regulate temperature-dependent diapause induction in B . mori using TALEN-mediated knockouts in the Kosetsu strain.…”
Section: Resultsmentioning
confidence: 99%